Does Molecular and Structural Evolution Shape the Speedy Grass Stomata? - Wang, Yuanyuan; Chen, Zhong-Hua (Frontiers in Plant Science, 2020)
It has been increasingly important for breeding programs to aim at crops that are capable to cope with a changing climate, especially higher frequency and intensity of drought events. Grass stomatal complex has been proposed as an important factor that may enables grasses to adapt to water stress and variable climate conditions. There are many studies focusing on the stomatal morphology and development mainly in the eudicot model plant Arabidopsis and monocot model plant Brachypodium. However, the comprehensive understanding of the distinction of stomatal structure and development between monocots and eudicots, especially between grasses and eudicots, are still less known at evolutionary and comparative genetic levels. Therefore, we employed the newly released version of One Thousand Plant Transcriptome (OneKP) database and existing databases of green plant genome assemblies to explore the evolution of gene families that contributed to the formation of unique structure and development of grass stomata. This review emphasizes the differential stomatal morphology, developmental mechanism, and guard cell signaling in monocots and eudicots. We provide a summary of useful molecular evidences for the high water use efficiency of grass stomata that may offer new horizons for future success in breeding climate resilient crops.